All normal dispersion nonlinear fiber source for Hyperspectral Stimulated Raman Scattering Microscopy - Abdolghader, Pedram; Pegoraro, Adrian F.; Joly, Nicolas; Ridsdale, Andrew; Lausten, Rune; Stolow, Albert (2019 Photonics North, PN 2019, 2019)
— we demonstrate the use a low noise all-normal-dispersion nonlinear fiber as a supercontinuum light source for Hyperspectral Stimulated Raman Scattering microscopy.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Low noise super continuum generation; Nonlinear microscopy; Stimulated Raman Microscopy